A taxonomical study on the Cladoceran and Copepod fauna in Pertek region of Keban Dam Lake - Tellioglu, Ayda; Yilmazturk, Yesim (Ege Univ, 2005)
Cladoceran and Copepod fauna in Pertek region of Keban Dam Lake was studied taxonomically from August 2002 - July 2003. At the and of this study, 4 species belonging to Cladoceran (Daphnia cucullata, Diaphanosoma mongolianum, Bosmina longirostris and Leptodora kindtii) and 3 species belonging to Copepods (Acanthodiaptomus denticornis, Arctodiaptomus osmanus and Cyclops vicinus) were determined 7 total species.
Keywords: Cladocera; Copepoda; Keban Dam Lake; taxonomy; zooplankton